Respuesta :

Answer:

Part 1) [tex]4m^{\frac{1}{2}}[/tex]

Part 2) [tex]3(r)^{\frac{1}{3}}(s)^{\frac{2}{3}}(t)^{\frac{4}{3}}[/tex]

Part 3) [tex]3(x)^{\frac{9}{4}}[/tex]

Step-by-step explanation:

Part 1) Write each expression without the radical.

we have

[tex]\sqrt{16m}[/tex]

we know that

[tex]16=4^2[/tex]

substitute

[tex]\sqrt{4^2m}[/tex]

Remember that

[tex]\sqrt[a]{x^b}=x^{\frac{b}{a}}[/tex]

[tex](x^a)^{b}=x^{ab}[/tex]

so

[tex]\sqrt{4^2m}=(4^2m)^{\frac{1}{2}}=(4^2)^{\frac{1}{2}}(m)^{\frac{1}{2}}=4m^{\frac{1}{2}}[/tex]

Part 2) Write each expression without the radical.

we have

[tex]\sqrt[3]{27rs^2t^4}[/tex]

we know that

[tex]27=3^3[/tex]

substitute

[tex]\sqrt[3]{3^3rs^2t^4}[/tex]

Remember that

[tex]\sqrt[a]{x^b}=x^{\frac{b}{a}}[/tex]

[tex](x^a)^{b}=x^{ab}[/tex]

so

[tex]\sqrt[3]{3^3rs^2t^4}=(3^3rs^2t^4)^{\frac{1}{3}}=(3^3)^{\frac{1}{3}}(r)^{\frac{1}{3}}(s^2)^{\frac{1}{3}}(t^4)^{\frac{1}{3}}=3(r)^{\frac{1}{3}}(s)^{\frac{2}{3}}(t)^{\frac{4}{3}}[/tex]

Part 3) Write each expression without the radical.

we have

[tex]\sqrt[4]{81x^9}[/tex]

we know that

[tex]81=3^4[/tex]

substitute

[tex]\sqrt[4]{3^4x^9}[/tex]

Remember that

[tex]\sqrt[a]{x^b}=x^{\frac{b}{a}}[/tex]

[tex](x^a)^{b}=x^{ab}[/tex]

so

[tex]\sqrt[4]{3^4x^9}=(3^4x^9)^{\frac{1}{4}}=(3^4)^{\frac{1}{4}}(x^9)^{\frac{1}{4}}=3(x)^{\frac{9}{4}}[/tex]

ACCESS MORE